The fir as a destructor of the forest communities in the Republic of Macedonia - Simovski, Bojan; Acevski, Jane (My University, 2012)
In the last 20-30 years in the forests in the Republic of Macedonia has been noted increasing presence of the fir. There are a number of factors that condition the spread of the fir, mainly the higher protection from the harmful effects of the anthropo-zoogenic factor, and changes in the environmental conditions. The spread of the fir is most intense in the zone of the beech forest region, but expansion is observed in the higher oak regions, too. This occurrence is a result of two main reasons: i) spread of the fir regarding natural regeneration; ii) spread of the fir by sowing fir seed in the beech and oak forest communities. The fir as a shade-tolerant species is the one which can survive and thrive as an understory of beech forests and it is capable to have a long time to rest awaiting the favourable moment for expansion in height. In the struggle for light in natural successive processes the fir manages to overcome the beech, which is confirmed by the fact that in high density beech forests the fir’s offspring successfully adapt to site conditions. Thus, it is evident the phytocoenological destructing role of the fir particularly in the beech forest communities in the Republic of Macedonia. In addition, the plant diversity in pure fir forests is poorer then in mixed fir forests. Confirmation of this finding are the data obtained from the management plans which shows the changing of the structure of the forests by composition and volume in favour of the fir.
Symposium presentation
Keywords: fir; spread; expansion; destructor; forest community